Kobieta wszechstronna utrwalona na łamach dwunastego numeru "Mojej Przyjaciółki" z 25 czerwca 1939 roku (uwagi lingwistyczno-kulturologiczne) = A versatile woman preserved in "Moja Przyjaciółka" issue 12, April 25, 1939 (linguistic-cultural remarks) - Węgorowska, Katarzyna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The subject of the text is a polemic against Andrzej Zawada`s thesis, who claims that one of the most popular women`s magazines "Moja Przyjaciołka. Ilustrowany Dwutygodnik Kobiecy" which appeared between 1934 and 1939 was addressed to "women of lower education".
Keywords: kobieta; czasopismo kobiece; wartość; wszechstronność; język; woman; woman`s magazine; values; versatility; language